A critical analysis of a large South African bank's commercial development property loan pre-disbursement conditions - Joubert, Chloe Louise (My University, 2008)
ABSTRACT The research question was to determine whether commercial property development loan pre-disbursement conditions protect the bank’s interests, or whether certain conditions hinder the pre-disbursement compliance process. The research showed that the majority of pre-disbursement conditions are of high importance in protecting the bank’s interests. However, findings were that not all conditions are important or even relevant for every project. Lack of understanding of the content and importance of the pre-disbursement conditions by the front-line consultant can lead to repetition and consequently an excessive number of conditions. The most important reason for delay in compliance with pre-disbursement conditions was identified as a lack of understanding by the client of the bank’s requirements and processes. Ignorance on the part of the developer of the bank’s procedures and requirements was also identified as the most common instance where relationships between the bank and the borrower were negatively affected by the pre-disbursement compliance process.
Keywords: bank; pre-disbursement; property; loan; development